The Drosophila decapentaplegic and short gastrulation genes function antagonistically during adult wing vein development. - Yu, K.; Sturtevant, M.A.; Biehs, B.; Francois, V.; Padgett, R.W.; Blackman, R.K.; Bier, E. (Development, 1996)
TGF-beta-related signaling pathways play diverse roles during vertebrate and invertebrate development. A common mechanism for regulating the activity of TGF-beta family members is inhibition by extracellular antagonists. Recently, the Drosophila short gastrulation (sog) gene was shown to encode a predicted diffusible factor which antagonizes signaling mediated by the TGF-beta-like Decapentaplegic (Dpp) pathway in the early blastoderm embryo. sog and dpp, which are among the earliest zygotic genes to be activated, are expressed in complementary dorsal-ventral domains. The opposing actions of sog and dpp in the early embryo have been highly conserved during evolution as their vertebrate counterparts, chordin and BMP-4, function homologously to define neural versus non-neural ectoderm in Xenopus. Here we exploit the genetically sensitive adult wing vein pattern to investigate the generality of the antagonistic relationship between sog and dpp. We show that dpp is expressed in vein primordia during pupal wing development and functions to promote vein formation. In contrast, sog is expressed in complementary intervein cells and suppresses vein formation. sog and dpp function during the same phenocritical periods (i.e. 16-28 hours after pupariation) to influence the vein versus intervein cell fate choice. The conflicting activities of dpp and sog are also revealed by antagonistic dosage-sensitive interactions between these two genes during vein development. Analysis of vein and intervein marker expression in dpp and sog mutant wings suggests that dpp promotes vein fates indirectly by activating the vein gene rhomboid (rho), and that sog functions by blocking an autoactivating Dpp feedback loop. These data support the view that Sog is a dedicated Dpp antagonist.